2021
DOI: 10.3390/rs13153034
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Mapping Grassland Plant Diversity with the Links among Spectral Diversity, Functional Trait Diversity, and Species Diversity

Abstract: Mapping biodiversity is essential for assessing conservation and ecosystem services in global terrestrial ecosystems. Compared with remotely sensed mapping of forest biodiversity, that of grassland plant diversity has been less studied, because of the small size of individual grass species and the inherent difficulty in identifying these species. The technological advances in unmanned aerial vehicle (UAV)-based or proximal imaging spectroscopy with high spatial resolution provide new approaches for mapping and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…However, the spectral diversity could tend to reach saturation, due to the increasing species richness with upscaling the window size, which might be similar to the empirical power-law relationship between the species richness and area [87]. For example, Zhao et al [35] found a tendency of gradual saturation based on the spectral characteristics when the species richness of grassland was above 17 within the estimation scale of 1.2 m × 1.2 m. Another study showed a contrary result that there was no saturated trend even when the species richness reached 50 within the windows of 60 m × 60 m, based on airborne data [32]. In addition, the window scale of diversity mapping is not only caused by the number of species, but also related to the environmental heterogeneity.…”
Section: Scales For Grassland Diversity Mappingmentioning
confidence: 87%
See 3 more Smart Citations
“…However, the spectral diversity could tend to reach saturation, due to the increasing species richness with upscaling the window size, which might be similar to the empirical power-law relationship between the species richness and area [87]. For example, Zhao et al [35] found a tendency of gradual saturation based on the spectral characteristics when the species richness of grassland was above 17 within the estimation scale of 1.2 m × 1.2 m. Another study showed a contrary result that there was no saturated trend even when the species richness reached 50 within the windows of 60 m × 60 m, based on airborne data [32]. In addition, the window scale of diversity mapping is not only caused by the number of species, but also related to the environmental heterogeneity.…”
Section: Scales For Grassland Diversity Mappingmentioning
confidence: 87%
“…The ability of spectral diversity calculated based on the bands which might be sensitive to specific biochemical characteristics even exceeds that of NDVI for grassland diversity monitoring (Figure 6). With the relationships among spectral diversity, functional diversity and species diversity of grassland being further explored [35], the optimal functional components could also be used for indicating the species diversity.…”
Section: Methods For Grassland Species Diversity Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Because differences in vegetation phenotypic characteristics correspond to variations in spectral band values (Spectral Variation Hypothesis; Palmer et al., 2002; Rocchini et al., 2004), spatio‐temporal variations in spectral bands (i.e., spectral diversity, SD) can be considered an indicator of spatio‐temporal variability of vegetation. This makes SD a cost‐ and time‐efficient proxy for different diversity facets (Surrogacy hypothesis; Gamon et al., 2020; Wang & Gamon, 2019), such as taxonomic diversity (TD, e.g., Conti et al., 2021; Marzialetti et al., 2021) and functional diversity (FD, e.g., Frye et al., 2021; Zhao et al., 2021).…”
Section: Introductionmentioning
confidence: 99%